Development of science subject-specific pedagogy to support disaster risk reduction in education: Its feasibility and influence - Nukhbatul Bidayati Haka; Luckyta Mauliana; Supriyadi Supriyadi; Abdul Hamid (Institut Agama Islam Negeri (IAIN) Palangka Raya Indonesia, 2023)
This development research aims to provide innovations to learning media in Biology learning. The model used in developing this media adopts the Borg & Gall development theory which is cut into 9 steps with a population of students in class XI MIPA. The instruments used are expert validation questionnaires, student response questionnaires, and critical thinking essay questions. The results of research in developing android-based virtual practicum media can improve critical thinking skills, become a simulation forum before carrying out activities in the laboratory (pre-lab), and become a solution to the shortage of laboratory facilities. The results of the validation of media experts get an average percentage of 91.66% with very decent criteria, material experts an average of 81.25% with very decent criteria, linguists produce 91.40% with very feasible criteria, and responses the percentage of students is 70.58% with proper criteria. The effectiveness of the media can be seen from the results of the hypothesis which gets Tcount   3.71 > Ttable 2.00, and also the N-Gain value of the experimental class which is greater than the control class, namely the experimental class gets a value of 0.63 while the control class is 0.25.